Detection of an endangered aquatic heteropteran using environmental DNA in a wetland ecosystem - Doi, Hideyuki (R Soc Open Sci, 2017)
The use of environmental DNA (eDNA) has recently been employed to evaluate the distribution of various aquatic macroorganisms. Although this technique has been applied to a broad range of taxa, from vertebrates to invertebrates, its application is limited for aquatic insects such as aquatic heteropterans. Nepa hoffmanni (Heteroptera: Nepidae) is a small (approx. 23 mm) aquatic heteropteran that inhabits wetlands, can be difficult to capture and is endangered in Japan. The molecular tool eDNA was used to evaluate the species distribution of N. hoffmanni in comparison to that determined using hand-capturing methods in two regions of Japan. The eDNA of N. hoffmanni was detected at nearly all sites (10 eDNA-detected sites out of 14 sites), including sites where N. hoffmanni was not captured by hand (five eDNA-detected sites out of six captured sites). Thus, this species-specific eDNA technique can be applied to detect small, sparsely distributed heteropterans in wetland ecosystems. In conclusion, eDNA could be a valuable technique for the detection of aquatic insects inhabiting wetland habitats, and could make a significant contribution to providing distribution data necessary to species conservation.